Pengaruh E-Service Quality dan Application Quality terhadap E-Loyalty melalui E-Satisfaction sebagai Mediasi: (Studi pada Mahasiswa Gen Z Pengguna Shopee Kota Bandung) - Mutiara Permatasari; Karyadi Karyadi; Ce Gunawan (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2026)
This study aims to analyze the influence of E-Service Quality and Application Quality on E-Loyalty, with E-Satisfaction as a mediating variable, among Generation Z students who use the Shopee app in Bandung. The rapid growth of e-commerce requires companies to understand the factors that can maintain customer loyalty amid intense digital competition. The research method used is quantitative with a descriptive and confirmatory approach. Data were collected through the distribution of questionnaires to 120 respondents selected using non-probability sampling techniques. Data analysis was conducted using Partial Least Squares (PLS)-based Structural Equation Modeling (SEM) to test the relationships among variables and the mediating effect. The results indicate that E-Service Quality and Application Quality have a positive and significant influence on E-Satisfaction. Furthermore, E-Service Quality, Application Quality, and E-Satisfaction were found to have a positive and significant influence on E-Loyalty. The mediation test results confirm that E-Satisfaction plays a significant role in mediating the influence of service quality and application quality on user loyalty. These findings indicate that to build long-term loyalty among Generation Z, Shopee must prioritize the technical quality of the application and the reliability of services capable of consistently creating user satisfaction.